Synchronous Modulation of Defects and Buried Interfaces for Highly Efficient Inverted Perovskite Solar Cells. Issue 3 (4th December 2022) - Xu, Yehui; Xiong, Shaobing; Jiang, Sheng; Yang, Jianming; Li, Dong; Wu, Hongbo; You, Xiaomeng; Zhang, Yefan; Ma, Zaifei; Xu, Jianhua; Tang, Jianxin; Yao, Yefeng; et al.
Abstract: Suppressing nonradiative recombination in perovskite solar cells (PSCs) is crucial for increases in their power conversion efficiency and operational stability. Here, it is reported that the synchronous use of a molecule daminozide (DA), as an interlayer and additive to judiciously construct a PTAA:F4TCNQ/DA/perovskite:DA hole‐selective heterojunction that diminishes thermionic losses for collecting holes at the buried interface between perovskites and PTAA:F4TCNQ, and reduces defect sites at such buried interfaces as well as in the perovskite film. The proposed "three birds with one stone" strategy significantly promotes charge transport, and both the interface carrier recombination and defect‐assisted recombination are suppressed. As a result, a remarkably improved efficiency of 22.15% and an impressive fill factor of 83.92% are achieved with excellent device stability compared to 19.04% of the control device. The two values are the highest records for polycrystalline MAPbI3 ‐based p‐i‐n structural PSCs reported to date. The work provides a promising approach of three birds with one stone, employing a functional material for further improvement of PSC performance. Abstract : Highly efficient state‐of‐the‐art perovskite solar cells via a "three birds with one stone" strategy are investigated. This strategy boosts power conversion efficiency and operational stability of the device.